Molecular and serological evidence of Borrelia burgdorferi sensu lato in wild rodents in the Czech Republic - Kybicová, K; Kurzová, Z; Hulínská, D (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2008)
The aim of the present study was to determine the frequency and spatial distribution of the Borrelia species in wild rodents in the Czech Republic. In total, 293 muscle tissue samples and 106 sera from 293 wild rodents captured in North Bohemia and North-East and South Moravia were examined for the presence of Borrelia spp. and antibodies. Muscle samples were investigated with real-time polymerase chain reaction (PCR) with a recA primer set, with DNA quantification and melting curve analysis, and with restriction fragment length polymorphism (RFLP) analysis of the 5S-23S rDNA intergenic spacer. Infection with Borrelia burgdorferi sensu lato was found in 16.4% of the muscle samples. The most abundant genospecies was Borrelia afzelii (11.3%), followed by Borrelia burgdorferi sensu stricto (4.8%) and Borrelia garinii (0.7%). Borrelia infection was more frequently observed in Clethrionomys glareolus than in Apodemus spp. Sera were analyzed with an enzyme-linked immunosorbent assay (ELISA) test, yielding the total seropositivity rates of 24.5% for anti-Borrelia IgM antibodies and 25.5% for IgG antibodies. Total seroprevalence was higher in Apodemus spp. than in C. glareolus. In conclusion, our data indicate that in the Czech Republic small wild rodents can serve as hosts for B. burgdorferi s. s. as well as for B. afzelii.
Keywords: hlodavci; infekce bakteriemi rodu Borrelia; Borrelia burgdorferi komplex; Immunoglobulin G; Seroepidemiologic Studies; séroepidemiologické studie; Immunoglobulin M; imunoglobulin M; Rodentia; Česká republika; Muscle, Skeletal; imunoglobulin G; Borrelia Infections; Borrelia burgdorferi Group; nemoci hlodavců; kosterní svaly; Czech Republic; Animals; zvířata; protilátky bakteriální; Rodent Diseases; Antibodies, Bacterial